2012
DOI: 10.1038/mt.2011.197
|View full text |Cite
|
Sign up to set email alerts
|

2A Peptide-based, Lentivirus-mediated Anti-death Receptor 5 Chimeric Antibody Expression Prevents Tumor Growth in Nude Mice

Abstract: Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL), a member of the TNF superfamily, induces tumor cell death via death receptors on target cells, without adverse effects on most normal cells. Its receptors are therefore an attractive target for antibody-mediated tumor therapy. Here, we report the creation of a lentivirus vector constructed by linking the heavy chain and the light chain of the antibody with a 2A/furin self-processing peptide in a single open reading frame that expresses a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…However, when we placed the LC gene upsreatm of the furin recognition site, we did not observe complete cleavage of furin. In agreement with our studies, several other investigations have also indicated that furin could not cleave efficiently when either LC or HC were arranged as a first cisteron [31, 44, 45]. Furthermore, different furin cleavage patterns were detected in the cell pools receiving either CHEF-F2A or CMV-F2A vectors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, when we placed the LC gene upsreatm of the furin recognition site, we did not observe complete cleavage of furin. In agreement with our studies, several other investigations have also indicated that furin could not cleave efficiently when either LC or HC were arranged as a first cisteron [31, 44, 45]. Furthermore, different furin cleavage patterns were detected in the cell pools receiving either CHEF-F2A or CMV-F2A vectors.…”
Section: Discussionsupporting
confidence: 92%
“…Considering these finding, it appears that factors other than the arrangement of the light and heavy chains affect the hydrolysis activity of furin. To give an illustration, Fang et al observed complete furin cleavage upon expression of mAb in vivo (Rat) [19] while furin could not cleave completely when mAbs were expressed in CHO and HEK 293T cells [31, 44, 45]. Also, some reports have demonstrated that secretory pathway of CHO cells is not able to provide sufficient amount of proteolytic enzymes to support the complete processing of the recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent designs have added a furin cleavage sequence upstream of 2A to eliminate the additional amino acids which would otherwise remain attached to the upstream protein after cleavage [32], [33]. Furin-2A (F2A) elements have been used for mAb expression in mammalian cells [32][36] and for in vivo gene therapy [37]. It has been demonstrated that the productivities of F2A-vector derived clones were comparable with those derived from an industry reference vector based on separate expression unit design [36].…”
Section: Introductionmentioning
confidence: 99%
“…18,21 However, incomplete cleavage of F2A was observed in some studies, resulting in HC-F2A-LC or LC-F2A-HC fusion proteins and LC and HC attached with F2A remnants. 18,27,30 The incorrectly processed peptides formed aggregates that could not be removed by protein A purification. 18 Besides F2A, E2A from equine rhinitis A virus, P2A from porcine teschovirus-1 and T2A from Thosea asigna virus have also been used widely in biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…26 F2A from the foot-andmouth disease virus, which is the most studied 2A, has been used for mAb expression in mammalian cells and for in vivo gene therapy. 18,21,[27][28][29][30][31] 2A peptides have approximately 20 amino acids and "self-cleavage" occurs between the last 2 amino acids, glycine (G) and proline (P). Adding a furin recognition sequence between the first gene and 2A aids in removing 2A residues from the upstream gene.…”
Section: Introductionmentioning
confidence: 99%